The Council of Economic Advisors: From Stabilization to Resource Allocation - Feldstein, Martin (American Economic Review, 1997)
This paper traces the changing role of the Council of Economic Advisers. In the 50 years since its creation, the CEA's focus has shifted from the design of policies to achieve full employment to one of advising on the much-enlarged spending and tax activities of the federal government. The CEA's original attention to achieving cyclical stability through fiscal policy diminished as economists changed their views about the inherent stability of the economy and the usefulness of fiscal policy. With the shift of macroeconomic policy to the Federal Reserve, the CEA's macroeconomic role has diminished but not disappeared. The rapid growth of government spending during the past five decades has greatly increased the role for the CEA in seeking efficient resource allocation.